Very early versus early referral for ablation in young patients with newly diagnosed paroxysmal atrial fibrillation. Issue 3 (23rd February 2022) - D'Angelo, Robert N.; Khanna, Rahul; Wong, Charlene; Yeh, Robert W.; Goldstein, Laura; Marcello, Stephen; Tung, Patricia; D'Avila, Andre; Zimetbaum, Peter J.
Abstract: Background: Catheter ablation (CA) has emerged as an effective therapy for the treatment of paroxysmal atrial fibrillation (AF); however it is unclear whether proceeding expeditiously to CA improves clinical outcomes in a real‐world population. This study compares outcomes of CA for new AF within 6 months of diagnosis (very early) 6 to 12 months after diagnosis (early) and 12 to 24 months after diagnosis (later). Methods: A large nationally‐representative sample of patients ages 18 to 64 who underwent CA from January 2011 to June 2019 was studied using the IBM MarketScan Database. The primary outcome was a composite of healthcare utilization over the following 24 months. Propensity score‐matching was used to match patients in each cohort. Risk difference in outcomes were compared between matched patients. Results: Two thousand six hundred thirty one patients were identified postmatching, with 1649 in the very early cohort and 982 in the early cohort. The very early referral group was less likely to experience the primary composite outcome postablation (Absolute risk difference [ARD]: −3.9%; 95% Confidence interval [CI]: −5.8%, −2.0%), with the difference driven by fewer cardioversions (ARD: −2.9%, 95% CI: −5.3%, −0.5%) and outpatient visits (ARD: −6.6%, 95% CI: −10.5%, −2.7%). There was no difference in outcomes between early and later referral groups, with only very early referral showing decreased healthcare utilization. Conclusions: Patients who underwent ablation within 6 months of diagnosis had lower healthcare utilization in the ensuing 24 months, driven by fewer outpatient visits and cardioversions, supporting expeditious referral for ablation for symptomatic AF.